Molecular characterization of coagulase-negative staphylococcus and biofilm- associated genes in S. capitis / Aziyah Abd Aziz - Abd Aziz, Aziyah (Institute of Graduate Studies, UiTM, 2015)
The coagulase-negative Staphylococcus (CoNS) is a group of bacteria that are gaining prominence as emerging pathogens of hospital-acquired infections. One such species is S. capitis, which is now the major cause of bloodstream infection especially in neonatal intensive units. The major virulence factor of S. capitis appears to be its ability to form a biofilm structure. A total of 200 local clinical isolates of CoNS was obtained from the Hospital Tuanku Ampuan Rahimah, Klang in between December 2010 to May 2011. Nine species of CoNS were identified with S. epidermidis, S. haemolyticus, S. hominis and S. capitis being the most prevalent strains. Identification of the isolates by biochemical tests using the Microgen Staph ID kit was less than 50% accurate while identification via the sodA gene sequence provided better discrimination and accuracy. The ERIC-PCR fingerprinting was then used to genotype the CoNS strains and the Discriminative Index (D) was calculated. At D = 0.949, ERIC-PCR can be used with confidence to discriminate between the S. hominis strains. However, low discriminative power (D < 0.9) was observed for S. capitis, S. epidermidis and S. haemolyticus implying that ERIC- PCR fingerprinting is not sufficient to genotype these strains. A multiplex PCR method was successfully developed to probe for the presence of icaABCD operon in a majority of the bacterial strains. At 88%, S. capitis showed the highest ability to form biofilm with a large percentage of these forming dense biofilm structures while the icaABCD operon was found to be present in all of the strains…